Structural and vibrational studies of fatty acids-functionalized iron oxide nanoparticles via alkaline co-precipitation route - Herrera W.T. (2015)
This work was supported by a grant (No. 013-2013) from the National Council of Science, Technology and Technological Innovation (CONCYTEC/FONDECYT-Peru). Ramos Guivar Juan A. is also grateful to FONDECYT (Grant No. 0218-2014).